Biomarkerless targeting and photothermal cancer cell killing by surface-electrically-charged superparamagnetic Fe3O4 composite nanoparticles. Issue 4 (12th December 2016) - Han, Xiao; Deng, Zicheng; Yang, Zi; Wang, Yilong; Zhu, Huanhuan; Chen, Bingdi; Cui, Zheng; Ewing, Rodney C.; Shi, Donglu
Abstract : A major challenge in cancer therapy is localized targeting of cancer cells for maximum therapeutic effectiveness. Abstract : A major challenge in cancer therapy is localized targeting of cancer cells for maximum therapeutic effectiveness. However, due to cancer heterogeneities, the biomarkers are either not readily available or specific for effective targeting of cancer cells. The key, therefore, is to develop a new targeting strategy that does not rely on biomarkers. A general hallmark of cancer cells is the much increased level of glycolysis. The loss of highly mobile lactate from the cytoplasm inevitably removes labile inorganic cations to form lactate salts and acids as part of the lactate cycle, creating a net of negative surface charges. This net of negative charges on cancer cell surfaces biophysically distinguishes themselves from normal cells. In this study, cancer cells are targeted by using positively-charged, fluorescent, superparamagnetic Fe3 O4 -composite nanoparticles. The positively-charged Fe3 O4 composite nanoparticles bind predominantly to cancer cells due to their negatively-charged surfaces. Upon electrical-charge-mediated Fe3 O4 nanoparticle binding onto cancer cells, irradiation by using an 808 nm laser is subsequently applied to induce photothermal hyperthermia that kills the cancer cells directly. The negatively-charged composite nanoparticles are found, however, not to target and bind the cancer cells due to the electrostatic repulsive force between them. This unique strategy paves a new path for effective targeting and direct cancer cell killing without relying on any biomarkers and anticancer drugs.